Peeling back the many layers of competitive exclusion - Maurer, John J.; Cheng, Ying; Pedroso, Adriana; Thompson, Kasey K.; Akter, Shamima; Kwan, Tiffany; Morota, Gota; Kinstler, Sydney; Porwollik, Steffen; McClelland, Michael; Escalante-Semerena, Jorge C.; Lee, Margie D. (Frontiers in Microbiology, 2024)
Baby chicks administered a fecal transplant from adult chickens are resistant to Salmonella colonization by competitive exclusion. A two-pronged approach was used to investigate the mechanism of this process. First, Salmonella response to an exclusive (Salmonella competitive exclusion product, Aviguard®) or permissive microbial community (chicken cecal contents from colonized birds containing 7.85 Log10 Salmonella genomes/gram) was assessed ex vivo using a S. Typhimurium reporter strain with fluorescent YFP and CFP genes fusions to rrn and hilA operon, respectively. Second, cecal transcriptome analysis was used to assess the cecal communities' response to Salmonella in chickens with low (<5.85 Log10 genomes/g) or high (>6.00 Log10 genomes/g) Salmonella colonization. The ex vivo experiment revealed reduction in Salmonella growth and hilA expression following co-culture with the exclusive community. The exclusive community also repressed Salmonella's SPI-1 virulence genes, LPS modification, while the anti-virulence/inflammatory gene avrA was upregulated. Salmonella transcriptome analysis revealed significant metabolic disparities in Salmonella grown with the two different communities. Propanediol utilization and vitamin B12 synthesis was central to Salmonella metabolism cocultured with either communities; and mutations in propanediol and vitamin B12 metabolism altered Salmonella growth with the exclusive community. There were significant differences in the cecal community, stress response to Salmonella colonization. Cecal community transcripts indicated that antimicrobials were central to the type of stress response detected in the low Salmonella abundance community suggesting antagonism involved in Salmonella exclusion. This study indicates complex community interactions that modulate Salmonella metabolism and pathogenic behavior and reduce growth by antagonism may be key to exclusion.